038 Detrimental effects of erythropoietin as an adjunct to PPCI: a randomised controlled trial in acute MI using cardiac MRI. (22nd September 2015) - Ludman, A J; Hasleton, J; Babu, G; Boston-Griffiths, E; Venugopal, V; Moon, J C; Muthurangu, V; Taylor, A M; Puranik, R; Yellon, D M; Hausenloy, D J
Abstract : Introduction: Animal studies have previously reported that the acute administration of erythropoietin (EPO) at the onset of myocardial reperfusion reduces infarct size by 40–50%. Whether EPO has the same effect in ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PPCI) is unknown. We aimed to assess the efficacy of EPO as adjunctive therapy to PPCI in STEMI patients using cardiac MRI. Methods: Fifty-one consenting STEMI patients presenting for PPCI within 12 h of chest pain were randomised to receive either a single intravenous bolus of EPO (50 000 iu in 10 ml normal saline) prior to PPCI with a further bolus given 24 h later, or placebo (10 ml normal saline prior to PPCI with a further bolus given 24 h later). Patients with TIMI flow>1, cardiac arrest, cardiogenic shock or significant coronary collateralisation to the area at risk, were excluded. Both patient and cardiologist were blinded to the treatment allocation. Troponin-T and CK-MB were measured over 24 h. CMR scans (LV volumes, LV ejection fraction- EF, late gadolinium enhancement- LGE, microvascular obstruction- MVO, infarct-endocardial surface area- ESA) were performed at day 3 and repeated at 4 months, and were analysed by two blinded observers. MACCE (cardiac death, stroke, target vessel revascularisation or hospital admission with acute coronary syndrome) were assessed at the 4-month follow-up. Results: There were no differences between groups in chest pain to balloon time or area at risk (AAR) assessed by either coronary angiography (modified BARI and APPROACH jeopardy scores) or CMR (infarct-ESA). Surprisingly, treatment with EPO doubled the incidence of MVO and acutely increased LV size (indexed LV end diastolic and systolic volumes: LVEDVi and LVESVi) on the acute CMR scan (see Abstract 38 Figure 1 and Abstract 38 Table 1 below). However, there were no significant differences in serum cardiac enzymes or CMR measured LVEF, myocardial infarct size, or the myocardial salvage index (see Abstract 38 Table 1 below). On the follow-up CMR scan at 4 months there were no significant differences in myocardial infarct size, LVEF and LV internal dimensions between the two treatment groups. There was no difference in MACCE between groups at 4 months follow up. The figure depicts representative early and late gadolinium enhancement short-axis images showing the presence of significant microvascular obstruction (see Abstract 38 Figure 1, *) within an area of infarction (see Abstract 38 Figure 2, arrow) in a patient presenting with an acute LAD myocardial infarct. Conclusions: In this randomised double blinded placebo-controlled clinical trial, EPO when administered as an adjunct to PPCI, doubled the incidence of MVO and acutely increased LV volumes. This study highlights the importance of cardiac MRI in assessing the safety and efficacy of new reperfusion treatment strategies.